The specter of the absurd : sources and criticisms of modern nihilism - Crosby, Donald A. (State University of New York Press, 1988)
This book is our century's most comprehensive and wise treatment of nihilism in all of its guises, comparing favorably with Rosen, Cavell, and indeed with Spengler. Crosby argues that our culture is genuinely haunted by nihilism expressing itself in the fideism of fundamentalism as well as in the debilitating alienation from all orientation. This results from a one-sided development of Western culture. The force of the argument derives from its comprehensive, cumulative character. Crosby distinguishes and relates five areas of nihilism: political, moral, epistemological, cosmic, and existential. Throughout the book, he illustrates and examines these as they are expressed in literature and art, in daily life and practical affairs, and in philosophy. The book is richly erudite in its marshalling of consciousness from so many domains.
Includes indexes.
Keywords: Nihilism (Philosophy); Nihilism.; Nihilisme (Politique); Nihilisme.; nihilism.; PHILOSOPHY -- Movements -- Deconstruction.; PHILOSOPHY -- History & Surveys -- General.; Nihilism; Das Absurde; Nihilismus